Effect of Prenatal Yoga on Duration of the First Stage of Labor and Perineal Rupture in Primigravida Mothers - Daniyati, Asri; Mawaddah, Shohipatul (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
In primigravidas, the first stage of labor has a longer duration than multiparous. The first stage of labor in primiparous is around 13-14 hours, while in multiparous it is about 7 hours. Prolonged labor is one of the causes of maternal death. Yoga in pregnancy can maintain elasticity and strength of the ligaments of the pelvis, hips, and leg muscles, so that it can reduce pain during labor and provide space for the birth canal. The comparative analytical research method used pre-experimental design with the one shot case study design. With a sample of 26 trimesters III primigravida pregnant women who were divided into 2 groups, namely n = 13 groups who did prenatal yoga, and n = 13 groups who did not do prenatal yoga. The analysis of this research was univariate and bivariate using the Mann Whitney test. Assessment is carried out during the delivery process. As a result, the intervention and control groups with active phase I labor duration obtained p = 0.000, and perineal rupture p = 0.000. There was a significant difference in the length of the first stage of labor and perineal rupture between the yoga group and the non-yoga group. Prenatal yoga affects the duration of the first stage of labor and perineal rupture.